Quality of Culinary Tourism Products Influence on Satisfaction and Loyalty of Tourists Visiting Puyung Inaq Esun Racing Rice Restaurant in Lombok - Martina, Claudia Dwi; Mananda, I Gusti Putu Bagus Sasrawan; Sudiarta, I Nyoman (Devotion : Journal of Research and Community Service, 2023)
This research was conducted on Nasi Balap Puyung Inaq Esun is a restaurant in central Lombok which is a restaurant that has been established since the 1970s and is the first nasi balap puyung in Lombok and adjacent to Mandalika tourist destinations. This study aims to analyze the effect of the quality of culinary tourism products on the satisfaction and loyalty of domestic tourists visiting Nasi Balapan Puyung Inaq Esun Lombok. This study uses quantitative research methods with a qualitative descriptive approach to describe the results of data analysis obtained from respondents. The sampling technique in this study uses purposive sampling techniques or determination of samples based on certain criteria, while the sample in question is an archipelago tourist who has visited Nasi Balap Puyung Inaq Esun Lombok. Data collection techniques in this study used questionnaires. The data analysis technique in this study uses the Structural Equation Model (SEM) with SmartPLS software development. The results showed that the quality of culinary tourism products has a significant or positive influence on the satisfaction of domestic tourists visiting Nasi Balap Inaq Esun, satisfaction has a significant effect on the loyalty of tourists visiting Nasi Balap Inaq Esun in Lombok, the quality of culinary tourism products has a significant influence on the loyalty of domestic tourists visiting Nasi Balap Inaq Esun,  and satisfaction is able to mediate between the quality of culinary tourism products with the loyalty of tourists visiting Nasi Balapan Inak Esun in Lombok.